773 LAPAROSCOPIC FUNDOPLICATION IN A DOG WITH GASTROESOPHAGEAL REFLUX DISEASE. (17th September 2021) - Edelmuth, Rodrigo; Hyndman, Philip; Spector, Daniel; Palma, Douglas; Greenberg, Jacques; Zarnegar, Rasa
Abstract: : Antireflux procedures in humans are well stablished. However, the veterinarian literature lack of information on antireflux procedures. To our knowledge, this is the first ever documented laparoscopic fundoplication performed on a canine. A one-year male, Belgian Malinois was presented for consultation of progressive chronic regurgitation and hypersalivation. Given the persistent clinical signs despite medical management, laparoscopic fundoplication was recommended and elected. Methods: Laparoscopic fundoplication was performed. The dog was induced under general anesthesia and prepared for ventral abdominal surgery in dorsal recumbency. A direct approach to the abdominal cavity was made just cranial to the umbilicus on midline and a 5 milimiter port placed routinely with a blunt trocar. Pneumoperitoneum was set at 8 to 10 millimeters of mercury. Results: The patient was hospitalized postoperatively receiving methadone, maropitant, ondansetron, erythromycin, metoclopramide, pantoprazole and intravenous crystalloid fluid therapy. A liquid/soft diet was offered from 17-hours postoperatively which the dog ate readily with a normal appetite. No vomiting nor regurgitation was noted during the dog's hospitalization. Patient was discharged 47 hours after surgery. Activity restriction was recommended for 14 days. The owner was recommended to adhere strictly to a diet comprised of a liquid consistency for the first seven days fed over three-to-four meals, followed by a slow gradual increase in consistency to canned soft food by three weeks. Conclusion: Reflux is probably more prevalent in canines than previously thought and possible implementation of antireflux testing and procedures may need to be considered in this population. Video: https://drive.google.com/file/d/1-H0rrRhsIXXSVaHM_iU1QVvr_BqPqIg2/view?usp=sharing .